PEG-Interferon-α ribavirin-induced HCV viral clearance: a pharmacogenetic multicenter Spanish study - Javier Milara; Maria Outeda-Macias; Mª Dolores Aumente-rubio; Patricio Más-Serrano; Azucena Aldaz; Mª Victoria Calvo; Mª Sergia García-Simón; Marisa Martin-Barbero; Núria Padullés-Zamora; Juan Antonio Schoenenberger; Marianne Saavedra-Aldrich; Enrique Tévar-Alfonso; et al. (Farmacia Hospitalaria)
Objective: Dual PEGylated interferon-(PEG-IFN) and ribavirin therapy has been the main hepatitis C virus (HCV) treatment of the last decade. Current direct-acting antiviral agents have improved the outcome of therapy but also have increased the cost and management complexity of treatment. The current study analyzes host genetics, viral and clinical predictors of sustained viral response (SVR) to dual PEG-IFN and ribavirin therapy in a representative Spanish population. Methods: Observational prospective multicentre pharmacogenetic cohort study conducted in 12 different hospitals of 12 different Spanish regions. A total of 98 patients with SVR and 106 with non-SVR in response to PEG-IFN and ribavirin therapy were included. 33 single nucleotide polymorphisms located in 24 different genes related with inflammatory, immune and virus response were selected. Clinical and viral data were also analyzed as candidate of SVR predictors. Results: IL-28B (rs12979860, rs7248668, rs8105790, rs8099917) and TNFRSF1B (rs1061622) genotypes, as well as TNFRSF1B/IL-10/TNF(-308) non-TTG and TNFRSF1B/IL- 10/IL-4 non-TTC haplotypes together with lower age, lower basal HCV RNA load, higher basal serum LDL cholesterol values, VHC genotypes 2 and 3 and basal low grade fibrosis 0-2 were associated with a SVR in the univariate analysis. Independent predictors of SVR in the multivariate analysis were IL-28B rs12979860 CC, TNFRSF1B/IL-10/IL-4 non-TTC along with low baseline HCV RNA load and HCV genotypes 2 and 3. Conclusions: IL-28B rs12979860 CC, TNFRSF1B/ IL-10/ IL-4 non-TTC haplotype, low baseline HCV RNA load and HCV genotypes 2 and 3 may help to predict successful outcome to PEG-IFN/ribavirin therapy in Spanish population